The Influence of Teacher Training on Participation in Co-Curricular Activities by Learners Who are Mentally Challenged in Special Units in Tigania West Sub-County Meru County - Imunya, Peter Thuranira; Mwenda, Gitonga Eric; Kubai, Kaberia Isaac (International Journal For Research In Educational Studies, 2018)
Learners who are mentally challenged participate in co-curricular activities to remain physically and emotionally healthy. Their participation is however limited due to special needs. The study sought to examine the influence of teacher training on participation by learners who are mentally challenged in co-curricular activities in special units in Tigania West Sub-county. The study could be beneficial to policy makers in the Ministry of Education, School management, learners who are mentally challenged and scholars. This study was guided by Alexander Astin's (1985) theory of Student Involvement. This study adopted the convergent parallel design. The target population for this study was 211 from 14 public primary schools with learners who are mentally challenged in Tigania West Sub-county, Meru County, Kenya. The sample size of the study was 138 respondents consisting of 14 head teachers, 14 BOM chairpersons, 23 special needs education teachers and 87 regular teachers. The study employed three sets of questionnaires: one for the head teacher, one for the special needs teachers and the other for the regular teachers and another for BOM chairpersons for data collection. Frequency tables and figures were used to present the quantitative data. Qualitative data was presented descriptively. The study established that teacher training enables the teacher to be child friendly, to be willing to work with children with mental challenges, to handle learners professionally and ensures learners will be motivated because the teacher has the skills. The study recommended that teachers in charge of learners with mental challenges should be well trained, and should motivate learners with mental challenges in order to enhance their participation in co-curricular activities.